Diverting children from a life of crime : measuring costs and benefits - Greenwood, Peter, W. (RAND, 1998)
In combating crime in America, little attention has been paid to keeping children from becoming criminals. What benefit might be realized from such an approach, and at what cost? Working from limited data on program efficacy and on criminal careers, the authors of this report made rough estimates of the costs and benefits of four early interventions--prenatal home visits by child care professionals, followed by four years of day care; training for parents with young children who have shown aggressive behavior; incentives to induce disadvantaged high-school students to graduate; and monitoring and supervising young delinquents. All except the first appeared to be at least as cost-effective as a popular but very different approach to crime reduction--California's "three-strikes" law. The advantages of parent training and graduation incentives in particular are so large that some advantage is likely to be found even under assumptions differing substantially from those made here. This report updates information contained in MR-699-UCB/RC/IF, published in 1996.